International hotel industry: F&B and bees / Irina Mohd Akhir ... [et al.] - Mohd Akhir, Irina; Mohd Mazlan, Mohd Azreen; Johari, Noorsa Riza; Hakim, Fairuz (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
In recent years, the hotel industry has witnessed a remarkable transformation with a significant focus on the ever- evolving food culture and trends. One aspect that has gained immense traction is the sourcing of local resources for food and beverages within the hotel industry. This paradigm shift towards supporting onsite productions has brought forth a multitude of benefits that cannot be overlooked. Embracing the concept of local resources, hotels are not only able to promote sustainability but also play a pivotal role in protecting the biodiversity and sustainability of the surrounding environment. This approach fosters a sense of responsibility towards the ecosystem, ensuring that the delicate balance of nature is maintained and preserved for future generations to enjoy.